Student Satisfaction In Objective Structured Clinical Examination (OSCE) At Nursing Students In Wamena - Sethiana Dewi Ruben (Sean Institute, 2023)
The target population in this research were students of SMA Negeri 2 The clinical trial evaluation assessment method is divided into interviews, written tests, observations and the implementation of OSCE. The OSCE evaluation method uses students displaying their competencies or abilities at various simulation stages to prove the extent of student competence in performing basic clinical competency skills, which are evaluated in the form of examinations. The satisfaction of examinees or students with the OSCE method can be seen through the achievement of the needs and expectations of examinees or students towards implementing OSCE. The study aims to determine student satisfaction with the Objective Structured Clinical Examination (OSCE). This descriptive research was conducted in the Wamena Nursing Study Program with a sample of 39 respondents. Respondents were given a questionnaire containing six aspects of student satisfaction, then analyzed using univariate analysis. The results of the student satisfaction research were obtained very satisfied as many as four respondents (10.3%), satisfied 23 respondents (59.0%), quite pleased happy as many as 11 respondents (28.2%) and dissatisfied as many as one respondents (2.6%). Tangibles aspect with an average student of 3.5. Responsiveness and empathy with an average of 3.4, Information System with an average of 3.2, and Assurance with an average of 3.1. It was concluded that most students were satisfied with the Objective Structured Clinical Examination (OSCE), the highest aspect of student satisfaction in reliability and the lowest in the element of Assurance